Acute effects of tissue flossing on boxers with chronic knee pain - Chen, Jie; Wang, Qirong; Zhao, Zhiguang; Song, Qipeng; Zhao, Peng; Wang, Dan (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectivesTo explore the acute intervention effects of tissue flossing on chronic knee pain (CKP) in boxers.MethodsEighteen boxers with CKP (12 male/6 female) were randomly divided into an experimental group (EG) with tissue flossing (n = 9) and a control group (CG) (n = 9). The visual analog scale (VAS), Lysholm knee function score, flexion range of motion (ROM), maximal isometric extensor muscle strength, and stability of the knee were measured pre- and post-intervention (EG: 3-minute tissue flossing, CG: rest).ResultsVAS (F = 15.849, p = 0.001, η2p = 0.498) and Lysholm knee function (F = 9.327, p = 0.008, η2p = 0.357) significantly improved more in the EG than in the CG. There was a significant difference for maximal isometric extensor muscle strength (F = 17.769, p = 0.001, η2p = 0.542) and knee stability (F = 13.844, p = 0.002, η2p = 0.464) but no significant difference for ROM (F = 1.218, p = 0.287, η2p = 0.075) between the EG and CG.ConclusionTissue flossing can reduce knee pain, improve knee function, increase knee extensor strength, and improve knee stability in boxers with CKP.